High dielectric and breakdown properties achieved in ternary BaTiO3/MXene/PVDF nanocomposites with low-concentration fillers from enhanced interface polarization. Issue 6 (15th April 2019) - Feng, Yefeng; Deng, Qihuang; Peng, Cheng; Wu, Qin
Abstract: Although high permittivity is achieved in barium titanate (BT) filled polymer nanocomposites, severely reduced insulation and breakdown properties are frequently found due to overload and agglomeration of BT nanoparticles with ultrahigh specific area. To simultaneously realize high permittivity and breakdown strength, in this work, unfunctionalized 2D Ti3 C2 MXene nanosheets with 2 wt% weight concentration were introduced to prepare ternary BT/MXene/polymer nanocomposites by solution cast process. Employing low-concentration conductive MXene instead of high-concentration ferroelectric BT could lead to significant improvement of permittivity of ternary composites, ascribed to remarkably increased interface types and enhanced interface polarization. In comparison to binary BT/polymer composites, ternary composites could have slightly improved dielectric loss and conductivity as well as gracefully reduced breakdown strength, attributed to finely retained high interface compatibility and filler dispersion. Ternary composite containing 8 wt% BT and 2 wt% MXene had a permittivity of 77, loss of 0.15 at 100 Hz and breakdown strength of 220 MV m −1 . This work might open the door to large-scale fabrication of promising composites with high permittivity and breakdown strength under low filler loading (~ 10 wt%).